Mousseau-Barbin tubes for benign strictures of the oesophagus - Holden, Michael P. (1971)
Two patients with benign strictures in the lower third of the oesophagus underwent insertion of Mousseau-Barbin tubes as palliative treatment for chronic dysphagia. The reasons for this particular form of treatment are discussed along with the unsatisfactory outcome.